Locus of control in mate choice: Etno-Psychometric validation - Padilla-Bautista, Joaquin Alberto (Pontificia Universidad Católica del Perú, 2017)
Today it seems as if each individual is responsible for choosing his/her mate. Historically, this process has been mainly regulated by culture, family and society, which make the rules and norms, and defines suitable behaviors in the mate selection process. This research aimed at constructing a scale to analyze if people consider themselves responsible for the choice of their partner and to what extent. A qualitative study using ATLAS.ti content analysis resulted in different theoretical factors. A second study sought to corroborate the theoretical factors using a principal component analysis, determining the following factors: Destiny-Predestination, Powerful Microcosm, and Internal Control factor, which explain 50.94% of the variance with 17 items. The instrument shows that the locus of control in mate choice is not a continuum that moves between internality and externality but, rather, it is multidimensional.